Assessment centre and its use in the corporate practice - Špatenková, Jana; Bedrnová, Eva, 1946-; Cipro, Martin, 1968-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
The goal of this master thesis is to summarise the theoretical knowledge and subsequently analyse the so-called Assessment Centre, a modern methodology used for recruitment of employees out of a larger pool of applicants. A unified approach to the recruitment process has been developed based on the results of this analysis The analysis includes a detailed insight into the preparation and the course of the Assessment Centre, a competency assessment of the committee members, assessment of the job description, job requirements and selection criteria and an analysis of satisfaction of the applicants themselves. The analysis was conducted on two workplaces of the Insurance Company "XY", with each of them having a different approach towards the assessment centre. Free as well as partially standardised observations were used as a methodological background for the assessment centre analysis. The assessment of satisfaction of the AC participants was conducted with the help of questionnaires.
Vedoucí práce: Eva Bedrnová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses